2021
DOI: 10.3390/polym13010158
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polymeric Materials: A Solution to Plastic Pollution from the Agro-Food Sector

Abstract: Conventional petroleum-derived plastics represent a serious problem for global pollution because, when discarded in the environment, are believed to remain for hundreds of years. In order to reduce dependence on fossil resources, bioplastic materials are being proposed as safer alternatives. Bioplastics are bio-based and/or biodegradable materials, typically derived from renewable sources. Food waste as feedstock represents one of the recent applications in the research field of bioplastics production. To date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 143 publications
(159 reference statements)
0
56
0
6
Order By: Relevance
“…Spectrophotometric assays have been largely used for the rough quantification of polyphenols and flavonoids. In the last decade, there has been an increasing request of more reliable and accurate analytical methods, with reduced operational time and costs, as well as with minimized use of hazardous chemicals [82][83][84][85], according to the green chemistry objectives [86]. The most common analytical methods used for the detection and/or quantification of the main classes of apples phytochemicals are the chromatographic ones.…”
Section: Methodsmentioning
confidence: 99%
“…Spectrophotometric assays have been largely used for the rough quantification of polyphenols and flavonoids. In the last decade, there has been an increasing request of more reliable and accurate analytical methods, with reduced operational time and costs, as well as with minimized use of hazardous chemicals [82][83][84][85], according to the green chemistry objectives [86]. The most common analytical methods used for the detection and/or quantification of the main classes of apples phytochemicals are the chromatographic ones.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have developed the abilities of other fibres to use in polymer composites, such as oil palm, sugarcane, roselle, kenaf, ginger, and bamboo [21][22][23][24][25][26][27]. The advances in implementing the methods used for biomaterial design focus on those derived from formulations based on fruit and vegetable by-products [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…These limitations occur due to the fact that chitosan is a naturally hydrophilic polymer, while PLA is hydrophobic. The elastic properties of chitosan could be improved by its plasticization with PEG [ 29 ], some resulting materials being stable until nine weeks of storage, as observed by Caner et al [ 30 ]. Butnaru et al [ 31 ] reported the preparation of films based on chitosan and cold-pressed rosehip seed oil by the encapsulation emulsion method.…”
Section: Introductionmentioning
confidence: 99%